Postoperative analgesic effects of intravenous, intramuscular, subcutaneous or oral transmucosal buprenorphine administered to cats undergoing ovariohysterectomy - Giordano, Tatiana [UNESP]; Steagall, Paulo V. M. [UNESP]; Ferreira, Tatiana H. [UNESP]; Minto, Bruno W. [UNESP]; Rodolfo de Sa Lorena, Silvia Elaine [UNESP]; Brondani, Juliana [UNESP]; Luna, Stélio Pacca Loureiro [UNESP] (Wiley-Blackwell, 2010)
ObjectiveTo compare the postoperative analgesic effects of intravenous (IV), intramuscular (IM), subcutaneous (SC) or oral transmucosal (OTM) buprenorphine administered to cats undergoing ovariohysterectomy.Study designRandomized, prospective and blinded clinical trial.Animals100 female cats.MethodsCats were assigned to receive 0.01 mg kg-1 of buprenorphine administered by the IV, IM, SC or OTM route (n = 25/group). Buprenorphine was made up to 0.3 mL with 0.9% saline. DIVAS (0-100 mm) and simple descriptive scale (SDS) (from 0 to 4) pain and sedation scores were assigned to each cat before and 1, 2, 3, 4, 6, 8, 12 and 24 hours after ovariohysterectomy. Buprenorphine and carprofen were administered for rescue analgesia. Data were analyzed using anova and Fisher's exact test (p < 0.05).ResultsThere were no significant differences between groups for breed, body weight, anesthetic time or surgery time (p > 0.05). There were no significant differences between groups for sedation scores at any time. SDS pain scores did not detect any differences between groups (p > 0.05). DIVAS pain scores after OTM administration were significantly higher than IV and IM administration at 1 hour and at 3, 4, 6, 8 and 12 hours, respectively (p < 0.05). DIVAS pain scores after SC administration were significantly higher than IV and IM administration at 2 hours and at 2, 3, 4, 8, 12 and 24 hours (p < 0.05), respectively. Six, four, 13 and 17 cats that received IV, IM, SC and OTM buprenorphine required rescue analgesia, respectively. There was a significantly higher incidence of treatment failure in cats that received SC and OTM buprenorphine compared with cats that received IV and IM buprenorphine (p < 0.05).Conclusions and Clinical relevanceIV and IM administration of buprenorphine provided better postoperative analgesia than SC or OTM administration of the drug and these routes of administration should be preferred when buprenorphine is administered to cats.
Keywords: analgesia; buprenorphine; cat; ovariohysterectomy; pain; routes of administration